Can gadget manage the classroom? - Jhoni Eppendi; Wandha Muliawaty; Aisyah Aisyah (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
The Pandemic is switching the teaching and learning process, which usually organizes face-to-face into a virtual setting. This condition initiated research to determine how the gadgets influence students' learning motivation and whether gadgets can manage face-to-face or not. The respondents were thirty-six addicted and seventy-four non-addicted gadgets of junior and senior high school students from five districts in North Kalimantan. The data collected was a closed questioner, and an interview was conducted virtually. The results showed that the gadget motivates the students since it enables all the respondents to practically access the material and minimizes respondents' anxiety in expressing the ideas. Discouragingly, the gadget could not take place in the face-to-face learning setting. Non-addicted and most addicted respondents claim that face-to-face learning builds direct interaction between peers and teachers, which cannot be found in online classes. Furthermore, the e-learning class supplies unmanageable assignments with the defective explained material. The class often holds asynchronously and gives fewer responses once the students ask for a detailed explanation. Furthermore, once the synchronous class is hosted, the internet connection distracts the class.